Amino acid sequence determination, in silico tertiary structure prediction and anticancer activity assessment of l-glutaminase from Bacillus cereus - Singh P.; Banik R.M.; Shah P. (My University, 2025)
Microbial glutaminase has been extensively used as antitumor drug in pharmaceutical industry from past few decades. The structural analysis based on homology modeling predicted a hypothetical 3D model structure for l-glutaminase from Bacillus cereus MTCC 1305 using peptide sequence data obtained from MALDI-TOF MS and template model of X-ray crystal structure of l-glutaminase from Bacillus subtilis (PDB: 1MKI_A). The model was found more reliable with 98.8 % residues in the favored region of Ramachandran plot. The predicted model structure was further refined using ANOLEA, QMEAN score and GROMOS 96 force field with total energy of −11,636.01 kJ/Mol and Z-score value as −1.41. Active site of predicted model was found to be enriched with 11 conserved amino acid residues like Ser73, ASN125, Asn176, Val270, Gln72, Cys204, Val270, Ser271, Tyr200, Lys76, Phe105, Tyr252. The docking approach showed good binding affinity of predicted model towards l-glutamine with favorable ΔG docking score. The anticancer activity of this enzyme was confirmed against colon carcinoma (HCT-116) cell line with IC50 value of 99.79 μg/ml. © 2016, Springer-Verlag Wien.